Assessment of metal leaching from rediset-polymer modified asphalt binder on groundwater and soil contamination. (June 2022) - Rahmad, Suzielah; Khahro, Shabir Hussain; Rosyidi, Sri Atmaja P.; Widyatmoko, Iswandaru; Memon, Naeem Aziz; Al-Sabaeei, Abdulnaser Mohammed; Milad, Abdalrhman; Sutanto, Muslich Hartadi; Yusoff, Nur Izzi Md.
Abstract: Road pavement is a structure that expose to various climate conditions. To make it more durable, modification of asphalt binder with polymer is a popular option. However, to maintain the environmental sustainability, the mixing and compaction temperature needs to be reduced. Warm Mix Asphalt additive had been widely used for this purpose. In this research, the impact of a polymer modified asphalt binder, PG76 together with a chemical WMA additive, Rediset on groundwater and soil contamination was investigated. The effect of Rediset on PG76 in terms of viscosity and activation energy was also studied via the rotational viscosity test. Even though it was found that Rediset might affect the viscosity of PG76, the activation energy shows independent values. ATR-FTIR was employed to understand the reaction between these two substance. It was found that there had been no chemical reaction between PG76 and Rediset. As a complementary, AFM was utilised to observe the surface characteristics at micro-scale. It appeared that Rediset did contribute to the binder's surface morphology. Finally, the modified tank leaching test together with analysis by ICP-MS, discovered that after 64 days submerged under flood, Rediset-PG76 had no effect on the adjacent water source and soil.